Birthmarked - O'Brien, Caragh M. (Roaring Brook Press, 2010)
In a future world baked dry by the sun and divided into those who live inside the wall and those who live outside it, sixteen-year-old midwife Gaia Stone is forced into a difficult choice when her parents are arrested and taken into the city.